Tetramethylpyrazine alleviates cerebral ischemia-reperfusion injury via NRF2/HO-1/GPX4-mediated ferroptosis inhibition - Hengpei Gong; Yinjun Lu; Lingfeng Wang; Xueyuan Gong; Jingfang Zhao; Zhenxin Li (Tissue and Cell, 2027)

Clay mineral evidence for sediment provenance and the evolution of the East Asian Winter Monsoon in the central Philippine Sea over the last 4.38 Ma - Jun Sun; Fei Guo; Huaichun Wu; Wei Huang; Jian Liu; Kai Lu; Jingfang Lu; Shuang Sun; Meinan Shi; Boya Li; Liwei Liu; Xiaoke Qiang (Global and Planetary Change, 2026)

Lanthanide-polyoxometalate-based anti-swelling luminescent conductive organohydrogel for information encryption and underwater sensing - Xinyu Lu; Jingfang Li; Min Gao; Sicong Zhao; Guangming Li (Chemical Engineering Journal, 2026)

To be integrated or not? Understanding continuance behavioral intention towards integrated ride-hailing services: Empirical evidence from Nanjing, China - Ke Lu; Jingfang Hu; Tingyu Shang; Yuan Xu (Sustainable Cities and Society, 2026)

The individual and combined effects of coastline changes and riverine input on water quality: A multi-scenario simulation perspective - Jingfang Lu; Wei Zheng; Dehai Song; Xianqing Lv; Weimin Wang; Honghua Shi (Marine Pollution Bulletin, 2025)

The roles of flaxseed gum and its oligosaccharides as stabilizers in zein nanoparticles for apigenin delivery: Stability, antioxidant activity, bioavailability, molecular simulations - Yufei Liu; Ziliang Li; Shuaijun Lu; Shang Gao; Mengting Xu; Ze Yuan; Yue Li; Yiqiao Gao; Jingfang Shangguan; Xia Xiang (Food Chemistry, 2025)

Protective effect of astragaloside IV against zinc oxide nanoparticles induced human neuroblastoma SH-SY5Y cell death: a focus on mitochondrial quality control - Liwei Wang; Lu Zhang; Yang Yun; Tingting Liang; Chaoqun Yan; Zhuoya Mao; Jingfang Zhang; Baoshe Liu; Jian Zhang; Taigang Liang (Molecular and Cellular Biochemistry, 2025)

Enhanced AGS by granular activated carbon loaded with nano iron when treating low strength and low COD/TN ratio municipal wastewater: Microbial metabolism, electron transfer and enhancement mechanism - Lei Peng; Haibo Li; Jianbo Guo; Jingfang Lu; Yanan Hou; Yi Han; Daohong Zhang; Yuanyuan Song; Jianhai Zhao (Journal of Environmental Chemical Engineering, 2024)

Preparation of Anderson-type CoMo6-2NH2@ECOF for highly active catalysis on aerobic oxidative desulfurization of fuel under O2 - Xue Lu; Jingfang Li; Liye Liang; Guangming Li (Fuel, 2024)

Quaternary pollen record and paleoenvironmental evolution of the Bohai Sea strait - Jingfang Lu; Wei Huang; Jun Sun; Feifei Wang; Yuexin Gao; Xin Fan; Daolai Zhang (Regional Studies in Marine Science, 2023)

A pervasive phosphorylation cascade modulation of plant transcription factors in response to abiotic stress - Wang Baoxiang; Sun Zhiguang; Liu Yan; Xu Bo; Li Jingfang; Chi Ming; Xing Yungao; Yang Bo; Li Jian; Liu Jinbo; Chen Tingmu; Fang Zhaowei; et al. (Planta, 2023)

Distribution of gold derived from hydrothermal fluids on the modern seafloor and its impact on the gold budget of seawater - Wei Huang; Jin Liang; Jingfang Lu; Fanghui Hou; Panfeng Li; Ruyong Cui (Frontiers in Marine Science, 2023)
The modern seafloor hydrothermal system plays a significant role in the cycling of energy and mass between the internal and external layers of the oceanic crust and upper mantle. It continues to supply hydrothermal fluids containing three to five orders of magnitude more gold into the ocean than the amount typically present in deep seawater. It has a considerable impact on the distribution and budget of gold with respect to the large geological inventory of the ocean along with other input sources such as river water. The large amount of various types of data compiled for this study reveals that only about 0.3% of the annual hydrothermal flux of gold (2618.3 kg/a) injected into the overlying seawater column as a dissolved phase is eventually trapped in sulfide deposits near vent sites on the seafloor, while about 0.8% is trapped in metalliferous sediments that fall out from the distal nonbuoyant plume. The remaining ~98.9% of gold is delivered into the depths of the global open ocean. The global budget of gold in seawater (about 1.4 × 10 7 kg), the annual flux of hydrothermal fluids at the seafloor (about 2.6 × 10 3 kg/a), the amount delivered by river water (about 7.2 × 10 4 kg/a), and significant estuarine removal (15%) allows us to estimate the residence time of gold in the modern ocean to be about 220 years. This value is 70% shorter than that (~1000 years) reported previously. In the future, the use of appropriate artificial means to achieve more efficient precipitation of gold from the hydrothermal system at the seafloor could increase the level of enrichment of gold to obtain gold-rich hydrothermal deposits, yielding greater economic benefits.

Spatio-temporal changes and driving forces of reclamation based on remote sensing: A case study of the Guangxi Beibu Gulf - Jingfang Lu; Yibo Zhang; Honghua Shi; Xianqing Lv (Frontiers in Marine Science, 2023)
Since 2000, coastal reclamation projects have been implemented in the Guangxi Beibu Gulf to alleviate the shortage of coastal land resources. As a result, the reclamation area has increased significantly. In this study, based on the Landsat program, we tracked coastal reclamation in the coastal waters of Guangxi in the 21st century. An indicator system was proposed to assess the driving forces of reclamation synthetically. Our results showed that 98.6 km 2 of coastal waters of the Guangxi Beibu Gulf was reclaimed from 1997 to 2017, in which three regions underwent great changes: Fangcheng Bay, Tieshan Bay, and Qiznhou Bay. Furthermore, spatio-temporal changes of reclamation were affected by the combination of population growth, economic development, and marine industry development in coastal cities. These results provide an important historical reference for tracking the human development processes of the Guangxi Beibu Gulf, and also offer some suggestions for the rational allocation of reclamation resources.

Coastal vulnerability modelling and social vulnerability assessment under anthropogenic impacts - Jingfang Lu; Yibo Zhang; Honghua Shi; Xianqing Lv (Frontiers in Marine Science, 2022)
Coastal regions are highly vulnerable to the impacts of human activities, land cover change, sea level rise (SLR), and climate extremes. In this study, we attempt to address this issue by simulating the spatial interactions among natural hazards, ever-increasing human activities, and social vulnerability in the south coast of the Bohai Sea, China. It is found that the activities occurring on land, especially within coastal environments, such as agricultural pond and ports, and those in the ocean (tide and residual current) both impose disaster risks on the marine environment. In 2020, 25.2% of the total study area is highly vulnerable, which is 21% larger than that in 1997. The socially vulnerable areas are mainly distributed in the southeast coast of the Laizhou Bay. These areas should be strengthened to reduce and prevent the storm surge and flood disasters. Ultimately, we emphasize the urgent needs to implement effective policy measures for reducing tomorrow’s risks from natural hazards.

Proper balance of omega-3 and omega-6 fatty acid supplements with topical cyclosporine attenuated contact lens-related dry eye syndrome - Ling Wang; Xi Chen; Jingfang Hao; Lu Yang (Inflammopharmacology, 2016)